Overexpression of cotton GhMKK4 enhances disease susceptibility and affects abscisic acid, gibberellin and hydrogen peroxide signalling in transgenic Nicotiana benthamiana. (26th August 2013) - Li, Yuzhen; Zhang, Liang; Lu, Wenjing; Wang, Xiuling; Wu, Chang‐Ai; Guo, Xingqi
Summary: Mitogen‐activated protein kinase (MAPK) cascades are involved in plant development, stress responses and hormonal signal transduction. MAPK kinases (MAPKKs), as the key nodes in these cascades, link MAPKs and MAPKK kinases (MAPKKKs). In this study, GhMKK4, a novel group C MAPKK gene from cotton ( Gossypium hirsutum ), was isolated and identified. Its expression can be induced by various stresses and signalling molecules. The overexpression of GhMKK4 in Nicotiana benthamiana enhanced its susceptibility to bacterial and fungal pathogens, but had no significant effects on salt or drought tolerance. Notably, the overexpressing plants showed increased sensitivity to abscisic acid (ABA) and gibberellin A3 (GA3), and ABA and gibberellin (GA) signalling were affected on infection with Ralstonia solanacearum bacteria. Furthermore, the overexpressing plants showed more reactive oxygen species (ROS) accumulation and stronger inhibition of catalase (CAT), a ROS‐scavenging enzyme, than control plants after salicylic acid (SA) treatment. Interestingly, two genes encoding ornithine decarboxylase (ODC) and S ‐adenosylmethionine decarboxylase (SAMDC), the key enzymes in polyamine synthesis, exhibited reduced R. solanacearum ‐induced expression in overexpressing plants. These findings broaden our knowledge about the functions of MAPKKs in diverse signalling pathways and the negative regulation of disease resistance in the cotton crop.